2017
DOI: 10.1002/rcm.7960
|View full text |Cite
|
Sign up to set email alerts
|

Time‐of‐flight secondary ion mass spectrometry using a new primary ion beam generated by vacuum electrospray of a protic ionic liquid, propylammonium nitrate

Abstract: The TOF-SIMS experiments confirmed that the propylammonium nitrate cluster ion beam was useful in generating molecular secondary ions, demonstrating that it is well suited for a primary ion beam in TOF-SIMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Fujiwara and coworkers reported that the massive cluster ion beam generated by the vacuum electrospray of a protic ionic liquid was useful in increasing protonated molecular species. 20 ) Massive gold cluster ions have been studied using LMIS techniques by several research groups. 21 ) Precursor peptide molecular ion yield enhancements of 1,000 were measured by comparing SIMS spectra obtained using Au + and Au 4+ 400 primary ions, 22 ) and very high secondary ion yields (>1) were also obtained for various biomolecules in experiments run in the event-by-event bombardment-detection mode.…”
Section: Introductionmentioning
confidence: 99%
“…Fujiwara and coworkers reported that the massive cluster ion beam generated by the vacuum electrospray of a protic ionic liquid was useful in increasing protonated molecular species. 20 ) Massive gold cluster ions have been studied using LMIS techniques by several research groups. 21 ) Precursor peptide molecular ion yield enhancements of 1,000 were measured by comparing SIMS spectra obtained using Au + and Au 4+ 400 primary ions, 22 ) and very high secondary ion yields (>1) were also obtained for various biomolecules in experiments run in the event-by-event bombardment-detection mode.…”
Section: Introductionmentioning
confidence: 99%